Composite mineralized wood fiber fireproof sandwich panel and preparation method thereof

CN122876709APending Publication Date: 2026-10-09ZHEJIANG YIHE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611189279.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,岩棉板表层由交错分布的矿物纤维构成,表层纤维之间的结合相对有限,容易发生掉渣、粉化和局部松散

Benefits of technology

[0023]本发明通过设置所述胶粘剂渗透固化层,无机阻燃胶粘剂渗入岩棉芯层表层纤维并固化,从而对岩棉表层纤维进行包覆、连接和固定,有效改善岩棉芯层表面的松散、掉渣和粉化风险;本发明通过在胶粘剂渗透固化层外侧设置耐碱玻璃纤维网格布,并使耐碱玻璃纤维网格布的至少部分玻璃纤维束嵌埋于矿化木纤维轻集料面层中,有助于提高面层抗裂性以及面层与岩棉芯层之间的连接稳定性,有效避免面层在干燥、养护、搬运、安装及受冲击过程中开裂或脱层的问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122876709A_ABST
    Figure CN122876709A_ABST
Patent Text Reader

Abstract

The application provides a composite mineralized wood fiber fireproof sandwich panel and a preparation method thereof. The composite mineralized wood fiber fireproof sandwich panel comprises a rock wool core layer, the rock wool core layer has a first surface and a second surface arranged oppositely; the first surface and the second surface are respectively provided with adhesive penetration and solidification layers, the adhesive penetration and solidification layers are formed by solidification of inorganic fire-retardant adhesive after the inorganic fire-retardant adhesive penetrates into the surface fibers of the rock wool core layer; the outer side of each adhesive penetration and solidification layer is provided with an alkali-resistant glass fiber mesh cloth, the outer side of each alkali-resistant glass fiber mesh cloth is provided with a mineralized wood fiber lightweight aggregate surface layer, and at least part of the glass fiber bundles of the alkali-resistant glass fiber mesh cloth are embedded in the corresponding mineralized wood fiber lightweight aggregate surface layer; the mineralized wood fiber lightweight aggregate surface layer is formed by solidification of mineralized wood fiber lightweight aggregate slurry. The application realizes effective fixation of the surface fibers of the rock wool core layer, stable connection of the surface layer and the core layer, crack resistance and flatness of the inorganic surface layer, and lightweight and stabilization of the overall structure of the sandwich panel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a fireproof sandwich panel and its preparation method, specifically to a composite mineralized wood fiber fireproof sandwich panel and its preparation method, belonging to the technical field of fireproof composite building panels. Background Technology

[0002] Rock wool boards possess good thermal insulation and non-combustible properties, making them widely used in fireproof components such as fire doors, fireproof partitions, and fireproof air ducts. However, the surface layer of rock wool boards is composed of interwoven mineral fibers, and the bonding between these fibers is relatively limited, making them prone to shedding, powdering, and localized loosening. When a mortar layer, decorative layer, or composite with other panels is formed directly on the surface of rock wool boards, the loose state of the surface fibers may lead to unstable interfacial bonding. Under conditions of transportation, installation, vibration, temperature changes, or external impact, the surface layer may crack, become hollow, or delaminate. Furthermore, the rough surface and insufficient flatness of rock wool boards are also detrimental to stable subsequent composite with metal panels, fire-retardant wood panels, or other decorative components.

[0003] Therefore, it is necessary to provide a composite sandwich panel that can penetrate and cure the surface fibers of the rock wool core layer, and form a stable double-sided composite structure through a mesh reinforcement structure and a mineralized wood fiber lightweight aggregate surface layer. While maintaining the basic functions of fire resistance and heat insulation, it also takes into account the lightweight, surface flatness and structural stability of the sandwich panel. It can be applied to fireproof door core panels, fireproof partition panels, fireproof air duct panels, prefabricated wall panels and other building components with requirements for fire resistance, heat insulation, surface flatness and structural stability. Summary of the Invention

[0004] Based on the above background, the purpose of this invention is to provide a composite mineralized wood fiber fireproof sandwich panel and its preparation method, which achieves effective fixation of the surface fibers of the rock wool core layer, stable connection between the surface layer and the core layer, crack resistance and flatness of the inorganic surface layer, and lightweighting and stabilization of the overall structure of the sandwich panel.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0006] A composite mineralized wood fiber fireproof sandwich panel includes a rock wool core layer, the rock wool core layer having a first surface and a second surface disposed opposite to each other; an adhesive penetration and curing layer is respectively provided on the first surface and the second surface, the adhesive penetration and curing layer being formed by an inorganic flame-retardant adhesive penetrating into the surface fibers of the rock wool core layer and then curing; an alkali-resistant glass fiber mesh is provided on the outer side of each adhesive penetration and curing layer, and a mineralized wood fiber lightweight aggregate surface layer is provided on the outer side of each alkali-resistant glass fiber mesh, at least a portion of the glass fiber bundles of the alkali-resistant glass fiber mesh being embedded in the corresponding mineralized wood fiber lightweight aggregate surface layer; the mineralized wood fiber lightweight aggregate surface layer is formed by curing a mineralized wood fiber lightweight aggregate slurry, the mineralized wood fiber lightweight aggregate slurry including inorganic cementitious materials, mineralized wood fibers and vitrified perlite lightweight aggregate.

[0007] Preferably, the penetration depth of the adhesive-cured layer into the rock wool core layer is 1-3 mm; and the thickness of each mineralized wood fiber lightweight aggregate surface layer is 5-10 mm.

[0008] Preferably, the inorganic flame-retardant adhesive comprises alkali metal silicates, phosphate curing components, and active inorganic fillers. The alkali metal silicates are one or a combination of sodium silicate and potassium silicate, and the active inorganic fillers are one or more of lightly calcined magnesium oxide, metakaolin, silica fume, and calcined kaolin.

[0009] Preferably, the inorganic cementing material is a magnesium oxysulfate cementing material or a low-alkali composite inorganic cementing material; the mineralized wood fiber lightweight aggregate slurry also includes one or more of the following: inorganic fine fillers, inorganic short fibers, setting regulators, water-retaining agents, water-reducing agents, and defoamers.

[0010] Preferably, the mineralized wood fiber is obtained by impregnating or spraying wood chips with a mineralizing solution, draining and drying, wherein the mineralizing solution includes one or more of silicate solution, borate solution, phosphate solution and lime milk.

[0011] Preferably, the density of the rock wool core layer is 100–180 kg / m³. 3 The thickness is 30-60 mm; the unit area mass of the alkali-resistant glass fiber mesh is 120-160 g / m². 2 The mesh size is 4mm×4mm~8mm×8mm.

[0012] Preferably, the rock wool core layer is provided with at least one receiving groove, and a mineralized wood reinforcing rib is embedded and fixed in the receiving groove, the mineralized wood reinforcing rib extending along the length of the board.

[0013] A method for preparing a composite mineralized wood fiber fireproof sandwich panel, the method comprising the following steps:

[0014] The rock wool board is cut and its surface is cleaned to obtain the rock wool core layer;

[0015] Inorganic flame-retardant adhesive is applied to the opposite two sides of the rock wool core layer, and the rock wool core layer is rolled to allow the inorganic flame-retardant adhesive to penetrate into the surface fibers of the rock wool core layer and form an adhesive penetration and curing layer.

[0016] Before the adhesive penetration curing layer is fully cured, alkali-resistant glass fiber mesh is applied to both sides of the rock wool core layer and then pressed together.

[0017] Prepare mineralized wood fiber lightweight aggregate slurry, wherein the mineralized wood fiber lightweight aggregate slurry comprises inorganic cementitious materials, mineralized wood fibers and vitrified perlite lightweight aggregate;

[0018] The mineralized wood fiber lightweight aggregate slurry is laid on the outer side of the two alkali-resistant glass fiber meshes respectively. The mineralized wood fiber lightweight aggregate slurry is formed into a mineralized wood fiber lightweight aggregate surface layer by limiting the thickness and rolling, and at least part of the glass fiber bundles of the alkali-resistant glass fiber mesh are embedded in the mineralized wood fiber lightweight aggregate surface layer.

[0019] The obtained composite board blank is dried, cured, trimmed, and inspected to obtain the composite mineralized wood fiber fireproof sandwich panel.

[0020] Preferably, when the inorganic flame-retardant adhesive is coated on the opposite surfaces of the rock wool core layer, the coating amount of the inorganic flame-retardant adhesive is 600–1200 g / m². 2 When the rock wool core layer is rolled, the pressure on the rolling contact surface is 0.1 to 0.3 MPa, and the number of rolling passes is 1 to 3. After the alkali-resistant glass fiber mesh is covered, it is pressed together with a rolling contact surface pressure of 0.02 to 0.05 MPa.

[0021] Preferably, when the mineralized wood fiber lightweight aggregate slurry is formed into a mineralized wood fiber lightweight aggregate surface layer by limiting thickness and rolling, the pressure of the rolling contact surface is 0.3 to 0.6 MPa, and the number of rolling passes is 1 to 3. When drying and curing the obtained composite board blank, it is first pre-dried at 50 to 70°C, and then cured at 20 to 35°C for 5 to 7 days.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] This invention, by setting the adhesive penetration and curing layer, allows the inorganic flame-retardant adhesive to penetrate into and cure the surface fibers of the rock wool core layer, thereby coating, connecting, and fixing the surface fibers of the rock wool, effectively improving the risk of loosening, flaking, and powdering of the rock wool core layer surface. Furthermore, by setting an alkali-resistant glass fiber mesh on the outside of the adhesive penetration and curing layer, and embedding at least a portion of the glass fiber bundles of the alkali-resistant glass fiber mesh in the mineralized wood fiber lightweight aggregate surface layer, this invention helps improve the crack resistance of the surface layer and the connection stability between the surface layer and the rock wool core layer, effectively preventing cracking or delamination of the surface layer during drying, curing, handling, installation, and impact.

[0024] This invention utilizes a mineralized wood fiber lightweight aggregate slurry containing inorganic cementitious materials, mineralized wood fiber, and vitrified perlite lightweight aggregate to form a mineralized wood fiber lightweight aggregate surface layer. This helps to obtain a relatively lightweight and smooth inorganic surface layer, thus balancing the requirements for lightweight and surface smoothness of sandwich panels. The mineralized wood fiber lightweight aggregate surface layers on both sides form a symmetrical layered composite structure with the rock wool core layer, which helps to improve the overall structural stability of the panel and reduce the risk of warping.

[0025] This invention achieves effective fixation of the surface fibers of the rock wool core layer, stable connection between the surface layer and the core layer, lightweight crack resistance and flatness of the inorganic surface layer, and symmetrical stability of the overall structure. At the same time, the optional mineralized wood reinforcement further improves the bending stiffness and installation stability. It is suitable for various application scenarios such as fireproof door core panels, fireproof partition walls, fireproof air duct panels, and prefabricated wall panels. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0027] Figure 1 This is a schematic diagram of the cross-sectional structure of a composite mineralized wood fiber fireproof sandwich panel according to the present invention;

[0028] Figure 2 This is a schematic diagram of the composite mineralized wood fiber fireproof sandwich panel of Embodiment 1 of the present invention;

[0029] In the diagram: 1. Rock wool core layer; 2. Adhesive penetration and curing layer; 3. Alkali-resistant glass fiber mesh; 4. Mineralized wood fiber lightweight aggregate surface layer. Detailed Implementation

[0030] The technical solution of the present invention will be further described in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any modifications and / or alterations made to the present invention will fall within the protection scope of the present invention.

[0031] In this invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used are commercially available or commonly used in the art. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art. Unless otherwise specified, the components or equipment in the following embodiments are general standard parts or components known to those skilled in the art, and their structures and principles can be learned by those skilled in the art through technical manuals or conventional experimental methods.

[0032] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings. In this detailed description, numerous specific details are set forth to facilitate explanation and provide a thorough understanding of the embodiments of the present invention. However, one or more embodiments may be practiced by those skilled in the art without these specific details.

[0033] Example 1

[0034] like Figure 1 As shown, this embodiment provides a composite mineralized wood fiber fireproof sandwich panel, which includes a mineralized wood fiber lightweight aggregate surface layer 4, an alkali-resistant glass fiber mesh 3, an adhesive penetration and curing layer 2, a rock wool core layer 1, an adhesive penetration and curing layer 2, an alkali-resistant glass fiber mesh 3, and a mineralized wood fiber lightweight aggregate surface layer 4 arranged in sequence, forming a symmetrical layered composite structure.

[0035] Rock wool core layer 1 has a density of 100 kg / m³ 3 It is obtained by cutting a rock wool board with a thickness of 30mm and having a first surface and a second surface that are set opposite to each other.

[0036] The adhesive-penetrated curing layer 2 is formed by the inorganic flame-retardant adhesive penetrating into the surface fibers of the rock wool core layer 1 and then curing. The inorganic flame-retardant adhesive includes alkali metal silicates, phosphate curing components, and active inorganic fillers. In this embodiment, sodium silicate is selected as the alkali metal silicate, aluminum dihydrogen phosphate as the phosphate curing component, and lightly calcined magnesium oxide as the active inorganic filler. The above components are formulated into an inorganic flame-retardant adhesive according to conventional proportions in the art, with a coating weight of 600 g / m². 2 After coating the opposite two sides of the rock wool core layer 1 with the above-mentioned inorganic flame retardant adhesive, the layers are rolled using a roller pressing device. The pressure at the roller pressing contact surface is 0.1 MPa, and the number of roller pressing cycles is 1. This allows the inorganic flame retardant adhesive to penetrate into the gaps between the surface fibers of the rock wool core layer 1, forming an adhesive penetration and curing layer 2 with a penetration depth of 1 mm. The adhesive penetration and curing layer 2 covers, connects, and fixes some of the rock wool fibers.

[0037] Before the adhesive penetration and curing layer 2 is fully cured, alkali-resistant glass fiber mesh 3 is applied to both sides of the rock wool core layer 1. The unit area mass of the alkali-resistant glass fiber mesh 3 is 120 g / m². 2 The mesh size is 4mm×4mm. After application, it is pressed together with a roller pressure of 0.02MPa to ensure that the alkali-resistant glass fiber mesh 3 and the adhesive-penetrated curing layer 2 are tightly bonded.

[0038] Mineralized wood fiber lightweight aggregate slurry was prepared. Mineralized wood fiber was obtained by impregnating wood chips with a silicate solution, leaching, and drying. An inorganic cementitious material, mineralized wood fiber, and vitrified perlite lightweight aggregate were mixed. The inorganic cementitious material was selected as magnesium oxysulfate cementitious material, prepared from lightly calcined magnesium oxide and magnesium sulfate heptahydrate. In one example, by weight, the mineralized wood fiber lightweight aggregate slurry comprised 100 parts of magnesium oxysulfate cementitious material, 35 parts of mineralized wood fiber, 18 parts of vitrified perlite lightweight aggregate, and appropriate amounts of inorganic fine fillers, inorganic short fibers, setting regulators, water-retaining agents, water-reducing agents, and defoamers. After uniformly mixing the above solid components, water was added and stirred to form a mineralized wood fiber lightweight aggregate slurry suitable for laying and roll forming.

[0039] The aforementioned mineralized wood fiber lightweight aggregate slurry is laid on the outer sides of two alkali-resistant glass fiber mesh fabrics 3. Through thickness limiting and rolling, the mineralized wood fiber lightweight aggregate slurry forms a mineralized wood fiber lightweight aggregate surface layer 4 with a single-sided thickness of 5 mm. During rolling, the pressure at the rolling contact surface is 0.3 MPa, and the rolling is performed once. During the thickness limiting and rolling process, at least a portion of the glass fiber bundles of the alkali-resistant glass fiber mesh fabric 3 are embedded in the corresponding mineralized wood fiber lightweight aggregate surface layer 4, thereby forming a composite connection between the surface layer, mesh fabric, penetrating and curing layer, and rock wool core layer.

[0040] The obtained composite slab was dried and cured. It was first initially dried at 50℃, then cured at 20℃ for 7 days. After curing, the edges were trimmed and inspected to obtain the desired result. Figure 2 The composite mineralized wood fiber fireproof sandwich panel shown.

[0041] Example 2

[0042] This embodiment provides a composite mineralized wood fiber fireproof sandwich panel, whose basic layered composite structure is the same as that in Embodiment 1.

[0043] Rock wool core layer 1 has a density of 140 kg / m³ 3 It is obtained by cutting a rock wool board with a thickness of 45mm.

[0044] In this inorganic flame-retardant adhesive, potassium silicate is used as the alkali metal silicate, potassium dihydrogen phosphate is used as the phosphate curing component, and a combination of metakaolin and silica fume is used as the active inorganic filler. The coating weight of the inorganic flame-retardant adhesive is 900 g / m². 2 After coating, a roller pressing process with a contact surface pressure of 0.2 MPa and two roller pressing cycles is used to allow the inorganic flame retardant adhesive to penetrate into the surface fibers of the rock wool core layer 1, forming an adhesive penetration and curing layer 2 with a penetration depth of 2 mm.

[0045] The unit area mass of alkali-resistant glass fiber mesh 3 is 140 g / m. 2 The mesh size is 6mm × 6mm. After application, it is pressed together with a roller pressure of 0.03MPa on the contact surface.

[0046] In this embodiment, the inorganic cementing material is a low-alkali composite inorganic cementing material, specifically a cementing system formed by combining low-alkali sulfoaluminate cement and silica fume in a conventional ratio, or a cementing system formed by combining low-alkali silicate cement and metakaolin in a conventional ratio. Mineralized wood fiber is obtained by spraying wood chips with a borate solution, followed by leaching and drying. The mineralized wood fiber lightweight aggregate slurry comprises, by weight, 100 parts of low-alkali composite inorganic cementing material, 45 parts of mineralized wood fiber, 22 parts of vitrified perlite lightweight aggregate, and appropriate amounts of inorganic fine fillers, inorganic short fibers, setting regulators, water-retaining agents, water-reducing agents, and defoamers. The above-mentioned inorganic cementing material, inorganic fine fillers, inorganic short fibers, and additives are first mixed, then mineralized wood fiber and vitrified perlite lightweight aggregate are added, followed by water addition and stirring to form a mineralized wood fiber lightweight aggregate slurry suitable for laying and roll forming.

[0047] After laying the mineralized wood fiber lightweight aggregate slurry, a mineralized wood fiber lightweight aggregate surface layer 4 with a single-sided thickness of 8 mm is formed by thickness limiting and roller pressing. The roller pressing contact surface pressure is 0.45 MPa, and the roller pressing is performed twice. At least a portion of the glass fiber bundles of the alkali-resistant glass fiber mesh 3 are embedded in the mineralized wood fiber lightweight aggregate surface layer 4.

[0048] The obtained composite board blanks were dried and cured. Initial drying was performed at 60℃, followed by curing at 28℃ for 6 days. After curing, the edges were trimmed and inspected to obtain composite mineralized wood fiber fireproof sandwich panels.

[0049] Example 3

[0050] This embodiment provides a composite mineralized wood fiber fireproof sandwich panel with mineralized wood reinforcing ribs, which is suitable for large-format fireproof partition boards, prefabricated wall panels, or fireproof door core panels with high requirements for bending stiffness.

[0051] Rock wool core layer 1 has a density of 180 kg / m³ 3A 60mm thick rock wool board is cut to obtain the product. At least one receiving groove is pre-cut in the rock wool core layer 1, extending along the length of the board. Mineralized wood reinforcing ribs are embedded and fixed in the receiving groove. The mineralized wood reinforcing ribs are strip-shaped and extend along the length of the board. The mineralized wood reinforcing ribs can be fixed in the receiving groove using inorganic flame-retardant adhesives or inorganic cementing materials.

[0052] In this inorganic flame-retardant adhesive, the alkali metal silicate is a combination of sodium silicate and potassium silicate, the phosphate curing component is aluminum phosphate, and the active inorganic filler is calcined kaolin. The coating weight of the inorganic flame-retardant adhesive is 1200 g / m². 2 After coating, a roller pressing process with a contact surface pressure of 0.3 MPa and 3 passes is used to form an adhesive penetration and curing layer 2 with a penetration depth of 3 mm.

[0053] The unit area mass of alkali-resistant glass fiber mesh 3 is 160 g / m. 2 The mesh size is 8mm × 8mm. After application, it is pressed together with a roller pressure of 0.05MPa on the contact surface.

[0054] Mineralized wood fiber is obtained by impregnating wood chips with a mixture of phosphate solution and lime slurry, followed by leaching and drying. Magnesium oxysulfate cementitious material is selected as the inorganic cementing material. The mineralized wood fiber lightweight aggregate slurry, by weight, comprises 100 parts magnesium oxysulfate cementitious material, 50 parts mineralized wood fiber, 25 parts vitrified perlite lightweight aggregate, and appropriate amounts of inorganic fine fillers, inorganic short fibers, setting regulators, water-retaining agents, water-reducing agents, and defoamers.

[0055] The above-mentioned slurry was laid on the outer sides of the two alkali-resistant glass fiber meshes 3, and a mineralized wood fiber lightweight aggregate surface layer 4 with a single-sided thickness of 10 mm was formed by thickness limiting and roller pressing. The roller pressing contact surface pressure was 0.6 MPa, and the roller pressing was performed 3 times.

[0056] The obtained composite board blanks were dried and cured. Initial drying was performed at 70℃, followed by curing at 35℃ for 5 days. After curing, the edges were trimmed and inspected to obtain a composite mineralized wood fiber fireproof sandwich panel with mineralized wood reinforcing ribs.

[0057] Comparative Example 1

[0058] This comparative example provides a sandwich panel, the preparation method of which is the same as that in Example 1, except that:

[0059] Instead of applying an inorganic flame-retardant adhesive to the surface of the rock wool core layer and performing roller pressing and penetration, ordinary cement mortar is directly laid on the surface of the rock wool core layer, and alkali-resistant glass fiber mesh is laid in the cement mortar. However, the mesh is only located in the middle of the mortar layer and does not form an adhesive penetration and curing layer with the rock wool core layer. Furthermore, the mesh is not embedded in the transition layer that is in direct contact with the rock wool core layer.

[0060] Specifically, a density of 100 kg / m³ is used. 3 A 30mm thick rock wool core layer was laid, with ordinary silicate cement mortar, 5mm thick, directly laid on both sides. An alkali-resistant glass fiber mesh with a 4mm x 4mm mesh size was laid in the middle of the mortar layer. After drying and curing, a comparison board was obtained.

[0061] Comparative Example 2

[0062] This comparative example provides a sandwich panel, the preparation method of which is the same as that in Example 2, except that:

[0063] The mineralized wood fiber lightweight aggregate surface layer does not contain mineralized wood fiber or vitrified perlite lightweight aggregate. It only uses ordinary cement mortar as the surface material, and the alkali-resistant glass fiber mesh is only laid between the mortar layer and the adhesive penetration and curing layer. The glass fiber bundles are not embedded in the mortar surface layer by roller pressing.

[0064] Specifically, a density of 140 kg / m³ is used. 3 A 45mm thick rock wool core layer was coated with inorganic flame-retardant adhesive on both sides and rolled to form a penetrating and cured layer. After covering it with alkali-resistant glass fiber mesh, ordinary cement mortar with a thickness of 8mm was laid on the outside of the mesh. Deep rolling to embed the mesh was not performed. After drying and curing, a comparison board was obtained.

[0065] The plates prepared in Examples 1-3 and Comparative Examples 1-2 were placed under the same environmental conditions for 48 hours and then subjected to systematic testing according to the following methods:

[0066] Apparent density was determined by the multi-sample averaging method.

[0067] The flexural strength was determined by loading the sample at the middle using the three-point bending method, with the span being 10 times the sample thickness.

[0068] The bond strength between the surface layer and the core layer was determined using the vertical tensile method to record the peak value from the maximum tensile stress to the interface separation.

[0069] The shedding rate was determined by a standard impact test, which involved taking a 100mm×100mm sample, removing one side layer, vibrating it under specified amplitude and frequency conditions, and weighing the proportion of the mass of the loose fibers and particles that fell off to the mass of the original sample surface layer.

[0070] The thermal conductivity was measured using the steady-state flat plate heat flow meter method at an average temperature of 25°C.

[0071] The drying shrinkage rate was obtained by measuring the change in length before and after drying at a constant temperature of 40°C to constant weight.

[0072] The surface flatness was measured by placing a 2m straightedge against the board surface and determining the maximum gap.

[0073] The retention rate of high-temperature residual flexural strength was obtained by placing the sample at 600℃ for 30 minutes, allowing it to cool naturally to room temperature, and then testing its residual flexural strength again, comparing it with the initial flexural strength at room temperature.

[0074] The specific data comparison of the above test results is shown in Table 1.

[0075] Table 1 Comparison of performance test results of each embodiment and comparative example.

[0076]

[0077] According to the test data in Table 1, compared with Comparative Example 1, Example 1 showed significantly superior performance in terms of bond strength, slag shedding rate, surface smoothness, and high-temperature residual strength retention. In Comparative Example 1, because no adhesive penetration and curing layer was formed on the surface of the rock wool core layer, ordinary cement mortar directly contacted the surface fibers of the rock wool, with only point contact and physical overlap at the interface, lacking effective chemical anchoring and fiber coating. The surface fibers of the rock wool were in a three-dimensional loose state. In the standard impact vibration test, a large number of unrestrained fibers fell off the surface of the core layer, with a slag shedding rate as high as 9.2%. At the same time, the cement mortar could not penetrate into the fiber gaps to form a transition layer, resulting in an interfacial bond strength of only 0.06 MPa. During flexural loading, the surface layer and the core layer almost experienced interfacial slippage and separation in the elastic stage, with a macroscopic flexural strength of only 2.2 MPa.

[0078] In Example 1, an inorganic flame-retardant adhesive composed of sodium silicate, aluminum dihydrogen phosphate, and lightly calcined magnesium oxide was used at a concentration of 600 g / m³. 2The coating is applied to the surface of the rock wool core layer and penetrates into the interstices of the surface fibers through a roller press at 0.1 MPa, forming an adhesive-infiltrated and cured layer with a penetration depth of 1 mm. The sodium silicate matrix undergoes condensation curing under the synergistic effect of the phosphate curing component and active filler, not only forming a three-dimensional coating and chemical fixation of the rock wool fibers, reducing the shedding rate to 0.28%, but also exhibiting high surface roughness and chemical activity after curing, providing a strong bonding substrate for the subsequent application of alkali-resistant glass fiber mesh. The mesh is pressed together before the adhesive is fully cured, forming a dual effect of chemical bonding and mechanical interlocking with the adhesive-infiltrated and cured layer. Subsequently, mineralized wood fiber lightweight aggregate slurry is laid on the outside of the mesh and rolled, embedding at least a portion of the glass fiber bundles of the mesh into the mineralized wood fiber lightweight aggregate surface layer, thereby forming a progressive composite transition structure between the rock wool core layer and the outer mineralized wood fiber lightweight aggregate surface layer. This transition structure gradually transfers stress from the brittle inorganic surface layer to the rock wool core layer through the flexible mesh reinforcement layer, avoiding stress concentration at the interface. As a result, the bonding strength of Example 1 reaches 0.28 MPa, which is about 4.7 times that of Comparative Example 1, the flexural strength is increased to 5.8 MPa, and the surface flatness is significantly improved from 3.6 mm to 1.3 mm.

[0079] Compared to Comparative Example 2, Example 2 exhibits significantly superior performance in terms of apparent density, thermal conductivity, drying shrinkage, flexural strength, and high-temperature residual strength retention. Although Comparative Example 2 included an adhesive-penetrating curing layer, the surface layer used ordinary silicate cement mortar, and the alkali-resistant glass fiber mesh was only laid flat at the interface and not embedded within the surface layer. The high apparent density of the ordinary cement mortar resulted in an overall density of 655 kg / m³ for Comparative Example 2. 3 The thermal conductivity reaches 0.095 W / (m·K), which is much higher than the 405 kg / m of Example 2. 3 The result is 0.062 W / (m·K). This is because Example 2 uses a low-alkali composite inorganic cementitious material and incorporates mineralized wood fiber and vitrified perlite lightweight aggregate. Vitrified perlite is a closed-cell glassy lightweight aggregate; its internal closed pores effectively block heat transfer, reducing the thermal conductivity contribution of the surface layer. After mineralization treatment with borate solution, the surface of the mineralized wood fiber forms an inorganic mineral layer, which not only reduces flammability but also improves its interfacial compatibility with the inorganic cementitious material, allowing the wood chips to play a lightweight filling and toughening role in the slurry. At the same time, the introduction of mineralized wood fiber and vitrified perlite reduces the net amount of cementitious material per unit volume, and the hydration products of the low-alkali composite inorganic cementitious material are more stable than those of the high-alkali system. The synergy of these two factors results in a drying shrinkage rate of only 0.48 mm / m in Example 2, less than 51% of that in Comparative Example 2, effectively suppressing internal cracks and interfacial peeling caused by drying shrinkage in the surface layer.

[0080] Furthermore, in Example 2, at least a portion of the glass fiber bundles of the alkali-resistant glass fiber mesh are embedded within the mineralized wood fiber lightweight aggregate surface layer. The mesh bears the tensile stress of the surface layer when bent, inhibiting crack initiation and propagation. In contrast, in Comparative Example 2, the mesh is only located at the interface plane, lacking a reinforcing skeleton within the surface layer, resulting in a flexural strength of only 4.9 MPa and a bond strength of 0.19 MPa. Under high-temperature conditions, the ordinary cement mortar surface layer undergoes volume shrinkage due to the dehydration of calcium hydroxide and the decomposition of ettringite, which is mismatched with the thermal expansion behavior of the rock wool core layer, leading to interface thermal stress concentration and surface layer cracking. The high-temperature residual flexural strength retention rate of Comparative Example 2 is only 45%. In contrast, the hydration products of the low-alkali composite inorganic cementitious material system in Example 2 are mainly low-alkali hydrated calcium silicate and aluminate, exhibiting higher heat resistance and stability. Furthermore, the vitrified perlite and mineralized wood fiber alleviate thermal stress transmission, and the mesh embedded within the surface layer further constrains deformation and cracking under high temperatures, resulting in a high-temperature residual flexural strength retention rate of 84%.

[0081] In Example 3, mineralized wood reinforcing ribs extending along the length of the board are installed inside the rock wool core layer. These ribs are embedded and fixed in the receiving groove. As shown in Table 1, the flexural strength of Example 3 reaches 11.2 MPa, which is 47% higher than that of Example 2 without reinforcing ribs. This is mainly because the mineralized wood reinforcing ribs bear the tensile or compressive stress across the neutral plane during bending. Their elongated structure forms an embedded skeleton along the length of the board, effectively reducing the compressive and tensile strain of the rock wool core layer during bending deformation, thereby significantly improving the overall flexural stiffness of the sandwich panel. At the same time, the bond strength and high-temperature residual flexural strength retention rate of Example 3 are further improved to 0.45 MPa and 88%, respectively, indicating that the introduction of reinforcing ribs does not damage the original interface structure. Instead, it reduces the shear stress at the interface between the surface layer and the core layer by sharing the load.

[0082] In summary, the composite mineralized wood fiber fireproof sandwich panel and its preparation method of the present invention exhibit a synergistic effect among their core features. Firstly, the anchoring effect of the inorganic flame-retardant adhesive penetration and curing layer on the surface fibers of the rock wool provides a chemically active and rough-structured substrate for the subsequent application of the alkali-resistant glass fiber mesh. Without this penetration and curing layer, as shown in Comparative Example 1, an effective transition cannot be formed between the mesh and the rock wool, resulting in near-complete loss of interfacial strength. Secondly, the application of the alkali-resistant glass fiber mesh before the adhesive is fully cured ensures a strong chemical bond and mechanical interlocking with the adhesive penetration and curing layer. Simultaneously, some glass fiber bundles of the mesh are embedded in the mineralized wood fiber lightweight aggregate surface layer, forming an interlocking structure between the surface layer and the core layer. This double-sided interlocking structure of the mesh allows the mineralized wood fiber lightweight aggregate surface layer and the rock wool core layer to no longer rely on a single planar interface, but rather form a progressive composite zone in the thickness direction, changing the stress transmission path from abrupt change to a continuous transition. Furthermore, the mineralized wood fiber lightweight aggregate surface layer uses low-alkali inorganic cementitious materials as the matrix and mineralized wood fiber and vitrified perlite as lightweight aggregates. This system not only has low density and low shrinkage, but also belongs to the same inorganic system in chemical composition as the alkali metal silicate-based adhesive penetration and curing layer. Its interfacial compatibility is much higher than that of organic adhesive systems. It will not produce organic volatilization and decomposition at high temperatures, thus ensuring fire resistance integrity and high-temperature structural stability.

[0083] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. A composite mineralized wood fiber fireproof sandwich panel, characterized in that: The composite mineralized wood fiber fireproof sandwich panel includes a rock wool core layer, which has a first surface and a second surface arranged opposite to each other. An adhesive penetration and curing layer is respectively provided on the first surface and the second surface. The adhesive penetration and curing layer is formed by an inorganic flame-retardant adhesive penetrating into the surface fibers of the rock wool core layer and then curing. An alkali-resistant glass fiber mesh is provided on the outer side of each adhesive penetration and curing layer, and a mineralized wood fiber lightweight aggregate surface layer is provided on the outer side of each alkali-resistant glass fiber mesh. At least a portion of the glass fiber bundles of the alkali-resistant glass fiber mesh are embedded in the corresponding mineralized wood fiber lightweight aggregate surface layer. The mineralized wood fiber lightweight aggregate surface layer is formed by curing a mineralized wood fiber lightweight aggregate slurry, which includes inorganic cementitious materials, mineralized wood fibers, and vitrified perlite lightweight aggregate.

2. The composite mineralized wood fiber fireproof sandwich panel according to claim 1, characterized in that: The penetration depth of the adhesive-cured layer into the rock wool core layer is 1-3 mm; the thickness of each mineralized wood fiber lightweight aggregate surface layer is 5-10 mm.

3. The composite mineralized wood fiber fireproof sandwich panel according to claim 1, characterized in that: The inorganic flame-retardant adhesive comprises alkali metal silicates, phosphate curing components, and active inorganic fillers. The alkali metal silicates are one or a combination of sodium silicate and potassium silicate, and the active inorganic fillers are one or more of lightly calcined magnesium oxide, metakaolin, silica fume, and calcined kaolin.

4. The composite mineralized wood fiber fireproof sandwich panel according to claim 1, characterized in that: The inorganic cementing material is a magnesium oxysulfate cementing material or a low-alkali composite inorganic cementing material; the mineralized wood fiber lightweight aggregate slurry also includes one or more of the following: inorganic fine fillers, inorganic short fibers, setting regulators, water-retaining agents, water-reducing agents, and defoamers.

5. The composite mineralized wood fiber fireproof sandwich panel according to claim 1, characterized in that: The mineralized wood fiber is obtained by impregnating or spraying wood chips with a mineralizing solution, draining and drying, wherein the mineralizing solution includes one or more of silicate solution, borate solution, phosphate solution and lime milk.

6. The composite mineralized wood fiber fireproof sandwich panel according to claim 1, characterized in that: The density of the rock wool core layer is 100–180 kg / m³. 3 The thickness is 30-60 mm; the unit area mass of the alkali-resistant glass fiber mesh is 120-160 g / m². 2 The mesh size is 4mm×4mm~8mm×8mm.

7. The composite mineralized wood fiber fireproof sandwich panel according to claim 1, characterized in that: The rock wool core layer is provided with at least one receiving groove, and a mineralized wood reinforcing bar is embedded and fixed in the receiving groove. The mineralized wood reinforcing bar extends along the length of the board.

8. A method for preparing a composite mineralized wood fiber fireproof sandwich panel, characterized in that: The method includes the following steps: The rock wool board is cut and its surface is cleaned to obtain the rock wool core layer; Inorganic flame-retardant adhesive is applied to the opposite two sides of the rock wool core layer, and the rock wool core layer is rolled to allow the inorganic flame-retardant adhesive to penetrate into the surface fibers of the rock wool core layer and form an adhesive penetration and curing layer. Before the adhesive penetration curing layer is fully cured, alkali-resistant glass fiber mesh is applied to both sides of the rock wool core layer and then pressed together. Prepare mineralized wood fiber lightweight aggregate slurry, wherein the mineralized wood fiber lightweight aggregate slurry comprises inorganic cementitious materials, mineralized wood fibers and vitrified perlite lightweight aggregate; The mineralized wood fiber lightweight aggregate slurry is laid on the outer side of the two alkali-resistant glass fiber meshes respectively. The mineralized wood fiber lightweight aggregate slurry is formed into a mineralized wood fiber lightweight aggregate surface layer by limiting the thickness and rolling, and at least part of the glass fiber bundles of the alkali-resistant glass fiber mesh are embedded in the mineralized wood fiber lightweight aggregate surface layer. The obtained composite board blank is dried, cured, trimmed, and inspected to obtain the composite mineralized wood fiber fireproof sandwich panel.

9. The method for preparing a composite mineralized wood fiber fireproof sandwich panel according to claim 8, characterized in that: When applying an inorganic flame-retardant adhesive to the opposite surfaces of the rock wool core layer, the coating amount of the inorganic flame-retardant adhesive is 600–1200 g / m². 2 When the rock wool core layer is rolled, the pressure on the rolling contact surface is 0.1 to 0.3 MPa, and the number of rolling passes is 1 to 3. After the alkali-resistant glass fiber mesh is covered, it is pressed together with a rolling contact surface pressure of 0.02 to 0.05 MPa.

10. The method for preparing a composite mineralized wood fiber fireproof sandwich panel according to claim 8, characterized in that: When the mineralized wood fiber lightweight aggregate slurry is formed into a mineralized wood fiber lightweight aggregate surface layer by limiting thickness and rolling, the pressure of the rolling contact surface is 0.3 to 0.6 MPa, and the number of rolling passes is 1 to 3. When drying and curing the obtained composite board blank, it is first pre-dried at 50 to 70°C, and then cured at 20 to 35°C for 5 to 7 days.